Holiday satisfaction in Penang, Malaysia: a quantitative perspective analysis of international and domestic tourists - Shida Irwana Omar,; Diana Mohamad,; Saliza Rozelee,; Badaruddin Mohamed, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
This study centres on tourists’ satisfaction level; with specific attention given to their experience and expectation of 20 holiday attributes during their visits to Penang. The study adapts the model of Holiday Satisfaction (HOLSAT) to measure the difference between experience and expectation of holiday attributes. The attributes employed are categorised into four groups, namely accessibility, accommodation, tourist amenities and food/meals. Results are drawn from a questionnaire survey of 4170 domestic and international tourists who visited Penang in 2014. The data is analysed quantitatively using matrices that show the mean score of expectation, plotted against the mean score of experience on a two-dimensional axis. The significance of the results is determined using a paired t-test at a scale of 1:1000. A similar pattern of satisfaction and dissatisfaction level was detected for international and domestic tourists. Overall, the study observed similar satisfaction and dissatisfaction patterns for all attribute groups, for both international and domestic groups. Despite a slight difference in p values, both accessibility and accommodation attributes performed excellently, except for attribute [3] ‘availability of information for tourists at entry points’ as perceived by the domestic group. However, the results for food/meals and tourist amenities should be of interest to tourism service providers as these are the attributes that need to be significantly improved upon and enhanced in order to increase tourists’ positive experience; especially for the domestic group. Specific attention should be directed towards conserving the ocean and beaches, as they house many of the main tourism developments and activities.